Editorial, Volume 14 (2019) - Oladipo Ojo, Dr. Emmanuel (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2019)
On behalf of the Editorial Board, it is with great pride and sincere privilege that I am writing this message to present the volume 14 (2019) of the JOURNAL OF SOCIAL SCIENCE RESEARCH. The issue comes from a long process, and we took all the necessary steps to make it a high-caliber scientific publication. We are relying on the collaboration of all our Editors, reviewers, and contributors to make it a contemporary, lively, and relevant publication.